Analysis of the Development of Tourism Villages as Community-Based Tourism to Attract Foreign Tourists to Indonesia After the Covid-19 Pandemic - Resa Rasyidah; Ahmad Zamzamy (Nusantara Science and Technology Proceedings, 2022)
Tourism is one of the main keys to Indonesia's economic development, especially after the Covid-19 pandemic. The Indonesian government through the Ministry of Tourism and Creative Economy (Kemenparekraf) was trying to develop sustainable tourism. One of these efforts is to develop the concept of a tourist village with the principle of community-based tourism. Community-based tourism can create a form of tourism that can provide opportunities for people to build their economy through tourism, in the long term. Several tourism villages have been developed and certified by the Kemenparekraf. These tourism villages that have been considered successful are then marketed to foreign countries, through international events such as exhibitions and tourism village competitions held by the UNWTO, ASEAN, and other international institutions.